Self-compassion as protective factor against emotion regulation difficulties, self-criticism and daily hassle among female college students - Eka Wahyuni; Wening Cahyawulan; Karsih karsih; Arga Satrio Prabowo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Female college students face several daily hassles along with their responsibility as a student especially during learning from home policy. The purpose of this study was to explore the role of self-compassion as a protective factor against emotion regulation difficulties and self-criticism among female students with consideration of their daily hassles. The correlative investigation model was employed in this study. The study sample was 870 female university students aged 17 to 24 years old. The correlation analysis indicated that daily hassle was positively correlated with emotion regulation difficulties and self-criticism. On the hand, emotion regulation difficulties, self-criticism, and daily hassle are negatively correlated with self-compassion. The path analysis indicated that increased daily hassle was directly associated with lower self-compassion, which in turn was associated with higher emotion regulation difficulties and self-criticism. Self-compassion was found to have a direct link to emotion regulation difficulties and self-criticism. Cultivation of self-compassion may have benefits for female college students to cope with their daily hassles.